Effect of Physalis Angulata L. Leaf Water Extract on Malondialdehyde (MDA) Testis, Calcium Intracellular Sperm and Total Motile Sperm of Male Wistar Rats (Rattus Novergicus) Model of Hypertension (Medico Legal Update, 2021)
Background: Determining the sperm quality can be measured by calculating sperm motility and spermmotility is governed by intracellular calcium (Ca2+) concentration. However, the intracellular calciumincrease found in essential hypertension cases may decrease acrosome reaction and increase ROS production,and may trigger sperm cell apoptosis. Ground cherry (Physalis angulata L) is an herbal plant containingbioflavonoid as antioxidant which is crucial to defend against free radicals and prevent toxic effects.Objective: This study aims to test the capacity of Physalis angulata L. extract, in preventing disruptionof sperm motility in male Wistar strain rats model of hypertension through oxidative stress reduction andcytosolic calcium regulation.Method: Experimental animal male white rat (Rattus novergicus) model of hypertension wereintraperitoneally inducted with L-NAME. The animals were divided into 5 treatment groups and givenPhysalis angulata L. leaf water extract with various doses for 14 consecutive days. At the end of the study,animals were sacrificed, and testes were taken for measuring the MDA levels, intracellular calcium, andsperm motility.Results: Physalis angulata L. leaf water extract is proven to prevent increasing number of testicular MDAlevel, prevent increasing number of sperm intracellular calcium, and prevent decreasing number of motilesperm in male white Wistar strain rat model of hypertension.Conclusion: The results show that the Physalis angulata L. leaf water extract is proven to prevent theincrease of MDA testis level and the increase of intracellular calcium testis amount, and prevent the numberof motile sperm on male Wistar strain white mice model of hypertension.